A Randomized Controlled Study to Determine the Efficacy of Garlic Compounds in Patients With Hematological Malignancies at Risk for Chemotherapy-Related Febrile Neutropenia. (September 2015) - Gatt, Moshe E.; Strahilevitz, Jacob; Sharon, Nir; Lavie, David; Goldschmidt, Neta; Kalish, Yossef; Gural, Alexander; Paltiel, Ora B.
Background . Patients receiving chemotherapy for hematological malignancies are at high risk for febrile neutropenia (FN). Garlic extracts (GEs) are natural food substances showing antimicrobial effects in vivo. Objectives . We explored whether adding GE may be efficacious in reducing the risk or severity of infections. Design . This was a placebo-controlled double-blind randomized study. Results . Of 95 patients randomized to receive GE or placebo following chemotherapy, a febrile episode was documented in 50% of patients receiving GE and 63.3% receiving placebo ( P = .89). There was a higher risk of developing a third and fourth febrile episode in the GE group ( P = .01). However, among those at a lower risk for FN, those receiving GE developed fewer FN episodes ( P = .075), especially those with severe neutropenia ( P = .05). Major adverse events were distributed equally, but nonadherence was more common in the GE than in the placebo group: 19.5% versus 4%, respectively ( P = .05). Conclusions . GE was safe and did not reduce FN risk in the entire cohort, but yet appeared to exert a protective effect in the lower-risk subgroup. We do not recommend the use of GE for FN prevention in higher-risk patients. A larger-scale clinical trial for the lower-risk subgroup of patients is advocated. (This trial was registered atwww.clinicaltrials.gov as NCT00247039.)